Psychological Determinants Influencing Women’s Entrepreneurial Orientation in Assam: The Significance of Self-Efficacy and Risk-Taking (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Entrepreneurship has become a global trend in today’s world. Fundamentally, a collection of psychological traits that allow people to take measured risks and overcome losses is what drives entrepreneurship. It has been stated in prior studies that entrepreneurs are mostly seen to have self-efficacy and risk-taking propensity. Assam, a thriving state in northeastern India, is becoming more acknowledged for its entrepreneurial spirit as a catalyst for job creation, economic expansion, and cultural preservation. In Assam, India, women entrepreneurs are becoming a significant force for empowerment, social transformation, and economic growth. The present study observes the relationship between self-efficacy, risk-taking, and entrepreneurial orientation among registered women entrepreneurs of Assam under the UDYAM registration portal. 346 samples were collected from two districts of lower Assam (Bongaigaon and Barpeta). Correlation and regression analysis state that both self-efficacy (SE) and risk-taking (RT) have a positive influence on women's entrepreneurial orientation (EO). Studies on this subject that take into account the region and the people are quite few. Because this study only looks at women entrepreneurs, it will be beneficial for the government and scholars to concentrate on women's empowerment in Assam. Even though the government has put in place many programs specifically for female entrepreneurs, very few of them are aware of them. Operating a firm requires more than just financial backing; it also requires the ability of business owners to successfully use their business acumen even in the face of reduced funding.